Electronic structure of graphene– and BN–supported phosphorene - Kistanov, Andrey A. (2019)
By using first–principles calculations, the effects of graphene and boron nitride (BN) substrates on the electronic properties of phosphorene are studied. Graphene–supported phosphorene is found to be metallic, while the BN–supported phosphorene is a semiconductor with a moderate band gap of 1.02 eV. Furthermore, the effects of the van der Waals interactions between the phosphorene and graphene or BN layers by means of the interlayer distance change are investigated. It is shown that the interlayer distance change leads to significant band gap size modulations and direct-indirect band gap transitions in the phosphorene–BN heterostructure. The presented band gap engineering of phosphorene may be a powerful technique for the fabrication of high–performance phosphorene–based nanodevices.